ADVANTAGES OF ASSESSMENT INDICATORS OF FINANCIAL STATEMENTS OF JOINT VENTURES - Yusupov Asror Makhmanazar Ogli (Scholar Express Journals, 2023)
The article describes the procedure for evaluating profitability, efficiency, liquidity, and financial stability indicators by analyzing financial reports of joint ventures.
Keywords: joint ventures; financial statements; assets